PERAN INTELEKTUAL CAPITAL DALAM PENINGKATAN KINERJA PERBANKAN SYARIAH DI INDONESIA - Putra, Purnama (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2015)
In the end of 2008, Bank Indonesia reported that Islamic Banking has grown as much as 40 % over Conventional Bank which has only 14 %. Islamic Banking has to solve the problems to maintain the stability of the growth so as it can achieve the market share target as much as 5 % per year. The problems faced are human resource, technology,and networking which are all sharia based. This research attemps to discribe the growth of human resources that is considered as undefined added value which is Intellectual capital (Mouritsen,2001) and optimalized it. It is caused by the huge gap between market value and book value disclosured by Enterprises. This problem is caused by the failure of the Enterprises in reporting their hidden value in the annual report (Brennan, 2001).Based on the library research that has been done, it is inferred that there are three categories of Intellectual Capital that have to be known by the Islamic Banking Stakeholder. The categories are human capital, relational capital and structural capital. Optimalizing Intellectual capital by developing Islamic human resources who have four competencies. The Competencies are Main competency, Behaviour Competency, Funtional competency and managerial competency.